2017
DOI: 10.1149/2.0351712jes
|View full text |Cite
|
Sign up to set email alerts
|

State of the Surface of Antibacterial Copper in Phosphate Buffered Saline

Abstract: The state was investigated of the copper surface in phosphate buffered saline (PBS; 140 mM Cl − , 10 mM phosphate; pH 7) by a combination of cyclic voltammetry (CV) and chronoamperometry (CA) with in situ spectroscopic ellipsometry and Raman spectroscopy. After polarization, samples were analyzed ex situ. In agreement with expectations on the basis of the Pourbaix diagram, Cu 2 O and Cu 4 O 3 were observed when polarizing the system above ≈−0.05 V vs. Ag|AgCl|3M KCl. The formation of Cu 2 O did not lead to a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…In former studies our group successfully employed in situ spectroscopic ellipsometry (SE) to probe metal supported oxide layer thicknesses simultaneously with spectral changes that can be attributed to composition changes in electrochemical setups. [24][25][26] It was shown that passive oxide films forming on Cu dissolve because of single charge oxygen vacancy formation during the OER. 25 In situ and operando measurements on metallic Cu showed that metastable Cu 4 O 3 forms before the oxide dissolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In former studies our group successfully employed in situ spectroscopic ellipsometry (SE) to probe metal supported oxide layer thicknesses simultaneously with spectral changes that can be attributed to composition changes in electrochemical setups. [24][25][26] It was shown that passive oxide films forming on Cu dissolve because of single charge oxygen vacancy formation during the OER. 25 In situ and operando measurements on metallic Cu showed that metastable Cu 4 O 3 forms before the oxide dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…27 Most importantly, the structure and properties of thin oxide films formed in electrochemical processes can significantly deviate from those found in the respective bulk system. [24][25][26][28][29][30] Different compositions and stability of different manganese oxides with respect to pH and electrode potential can be accessed through the Pourbaix diagram (cf. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…At the metal–electrolyte interface, the dissolution reaction must involve an oxidation, which could, for example, proceed via a localized reaction with oxygen to a soluble Cu 2+ species. [ 54,55 ]…”
Section: Discussionmentioning
confidence: 99%
“…At the metal-electrolyte interface, the dissolution reaction must involve an oxidation, which could, for example, proceed via a localized reaction with oxygen to a soluble Cu 2þ species. [54,55] Mott-Schottky analysis for copper indicates p-type behavior, and the positive photovoltage and cathodic photocurrent measurements indicate that electrons migrated toward the oxide-electrolyte interface. Therefore, a process where electrons contribute to accelerated cathodic reaction and thereby accelerate the corrosion rate is proposed.…”
Section: The Role Of Electron-hole Pair Formationmentioning
confidence: 99%
“…The decrease of Cu 4 O 3 peak is interpreted as transformation of Cu 4 O 3 to other copper oxides, presumably CuO, at higher electrode potential. (Alternatively, soluble Cu 2+ species may also form [47].) During the negative scan, the peak at 523 cm −1 increased, implying the reformation of Cu 4 O 3 .…”
Section: Inhibition Of Oxide Formationmentioning
confidence: 99%